Analytical Model for Light Modulating Impedance Spectroscopy (LIMIS) in All-Solid-State p-n Junction Solar Cells at Open-Circuit - Almora Rodriguez, Osbel; Miravet, Daniel; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Applied Physics Letters, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-known tool for characterization of materials and electronic devices. It can be complemented by numerical simulation strategies relying on drift-diffusion equations without any equivalent circuit-based assumptions. This implies the time-dependent solutions of the transport equations under small perturbation of the external bias applied as a boundary condition at the electrodes. However, in the case of photosensitive devices, a small light perturbation modulates the generation rate along the absorber bulk. This work then approaches a set of analytical solutions for the signals of IS and intensity modulated photocurrent and photovoltage spectroscopies, intensity modulated photocurrent spectroscopy (IMPS) and intensity modulated photovoltage spectroscopy (IMVS), respectively, from one-sided p-n junction solar cells at the open-circuit. Subsequently, a photoimpedance signal named “light intensity modulated impedance spectroscopy” (LIMIS = IMVS/IMPS) is analytically simulated, and its difference with respect to IS suggests a correlation with the surface charge carrier recombination velocity. This is an illustrative result and the starting point for future more realistic numerical simulations.<br

Capacitive Dark Currents, Hysteresis, and Electrode Polarization in Lead Halide Perovskite Solar Cells - Almora Rodriguez, Osbel; Zarazua, Isaac; Mas-Marza, Elena; Mora-Sero, Ivan; Bisquert, Juan; Garcia-Belmonte, Germà (Journal of Physical Chemistry Letters, 2015)
Despite spectacular advances in the conversion efficiency of perovskite solar cells many aspects of its operating modes are still poorly understood. Capacitance constituted to explore which mechanisms and functions. Analyzing capacitive responses in the device but also the kinetics of the charging processes and how they alter the solar cell current. Two main polarization processes are identified. Dielectric properties of the microscopic dipolar units through the orthorhombic-to-tetragonal phase transition account. Electrode polarization caused by interfacial effects, presumably related to kinetically slowness piled up in the vicinity of the outer interfaces, consistently explain the reported excess capacitance values ​​at low frequencies. In addition, current-voltage curves and capacitive responses of perovskite-based solar cells are connected. The observed hysteretic effect in the dark current originates from the slow capacitive mechanisms.<br
Keywords: Photovoltaics; lead halide perovskites; hysteresis; capacitance; electrode polarization

Characterization of Aerosol Deposited Cesium Lead Tribromide Perovskite Films on Interdigited ITO Electrodes - These, Albert; Khansur, Neamul Hayet; Almora, Osbel; Luer, Larry; Matt, Gebhard; Eckstein, Udo; Barabash, Anastasia; Osvet, Andres; Webber, Kyle Grant; Brabec, Christoph (Advanced Electronic Materials, 2021)
Aerosol deposition (AD) is a promising additive manufacturing method to fabricate low-cost, scalable films at room temperature, but has not been considered for semiconductor processing, so far. The successful preparation of cesium lead tribromide (CsPbBr3) perovskite films on interdigitated indium tin oxide (ITO) electrodes by means of AD is reported here. The 20–35 µm thick layers are dense and have good adhesion to the substrate. The orthorhombic Pnma crystal structure of the precursor powder was retained during the deposition process with no signs of defect formation. The formation of electronic defects by photoluminescence spectroscopy is investigated and found slightly increased carrier recombination from defect sites for AD films compared to the powder. A nonuniform defect distribution across the layer, presumably induced by the impact of the semiconducting grains on the hard substrate surface, is revealed. The opto-electronic properties of AD processed semiconducting films is further tested by electrical measurements and confirmed good semiconducting properties and high responsivity for the films. These results demonstrate that AD processing of metal halide perovskites is possible for opto-electronic device manufacturing on 3D surfaces. It is believed that this work paves the way for the fabrication of previously unimaginable opto-electronic devices by additive manufacturing.
CRIS-Team Scopus Importer:2021-01-22
Keywords: aerosol deposition; hysteresis; impedance spectroscopy; inorganic perovskites; photoluminescence spectroscopy

Comprehensive Investigation and Analysis of Bulk-Heterojunction Microstructure of High-Performance PCE11:PCBM Solar Cells - Zhang, Chaohong; Heumüller, Thomas; Gruber, Wolfgang; Almora, Osbel; Du, Xiaoyan; Ying, Lei; Chen, Junwu; Unruh, Tobias; Cao, Yong; Li, Ning; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Worldwide research efforts have been devoted to organic photovoltaics in the hope of a large-scale commercial application in the near future. To meet the industrial production requirements, organic photovoltaics that can reach power conversion efficiency (PCE) of over 10% along with promising operational device stability are of utmost interest. In the study, we take PCE11:PCBM as a model system, which can achieve over 11% PCE when processed from nonhalogen solvents, to deeply investigate the morphology− performance−stability correlation. We demonstrate that four batches of PCE11 with varying crystalline properties can achieve similar high performance in combination with PCBM. Careful device optimization is necessary in each case to properly address the requirements for the quite distinct microstructures. The bulk-heterojunction (BHJ) microstructure is comprehensively investigated as a function of the macromolecular weight and crystallinity. It is demonstrated that small differences in morphology significantly affect the kinetics and thermodynamic equilibrium of the BHJ microstructure as well as the photostability and thermal stability of the PCE11:PCBM solar cells<br
Keywords: in situ capacitance spectroscopy; organic photovoltaics; bulk-heterojunction microstructures; film morphology; PCE11:PCBM solar cells

Device Performance of Emerging Photovoltaic Materials (Version 1) - Almora, Osbel; Baran, Derya; Bazan, Guillermo C.; Berger, Christian; Cabrera, Carlos I.; Catchpole, Kylie R.; Erten-Ela, Sule; Guo, Fei; Hauch, Jens; Ho-Baillie, Anita W.Y.; Jacobsson, T. Jesper; Janssen, Rene A.J.; et al. (Advanced Energy Materials, 2020)
Emerging photovoltaics (PVs) focus on a variety of applications complementing large scale electricity generation. Organic, dye-sensitized, and some perovskite solar cells are considered in building integration, greenhouses, wearable, and indoor applications, thereby motivating research on flexible, transparent, semitransparent, and multi-junction PVs. Nevertheless, it can be very time consuming to find or develop an up-to-date overview of the state-of-the-art performance for these systems and applications. Two important resources for recording research cells efficiencies are the National Renewable Energy Laboratory chart and the efficiency tables compiled biannually by Martin Green and colleagues. Both publications provide an effective coverage over the established technologies, bridging research and industry. An alternative approach is proposed here summarizing the best reports in the diverse research subjects for emerging PVs. Best performance parameters are provided as a function of the photovoltaic bandgap energy for each technology and application, and are put into perspective using, e.g., the Shockley–Queisser limit. In all cases, the reported data correspond to published and/or properly described certified results, with enough details provided for prospective data reproduction. Additionally, the stability test energy yield is included as an analysis parameter among state-of-the-art emerging PVs.
CRIS-Team Scopus Importer:2020-12-11
Keywords: bandgap energy; emerging photovoltaics; flexible photovoltaics; photovoltaic device photostability; transparent and semitransparent solar cells

Device Physics of Hybrid Perovskite Solar Cells: Theory and Experiment - López-Varo, Pilar; Jiménez-Tejada, Juan A.; García-Rosell, Manuel; Garcia-Belmonte, Germà; Bisquert, Juan; Almora Rodriguez, Osbel (Advanced Energy Materials, 2018)
Perovskite solar cells exhibit a series of distinctive features in their optoelectronic response that have a decisive influence on the performance, especially for long-time response. Here is a survey of recent advances both in device simulation and optoelectronic and photovoltaic responses are provided, with the aim of covering comprehensively recent advances. Device simulations are included with clarifying discussions about the implications of classical drift-diffusion modeling and the inclusion of ionic charged layers near the outer carrier selective contacts. The outcomes of several transient techniques are summarized, along with the discussion of impedance and capacitive responses. In relation to the capacitive response, it is also a discussion on the hysteresis curve. Although alternative models and explanations are included in our discussion, the review relies upon a key mechanism. 20%, outer interfaces play a role in the performance of the PSCs. The ionic and electronic kinetics in the vicinity of the interfaces, coupled to surface recombination and carrier extraction mechanisms, should be carefully explore
Keywords: perovskite solar cell impedance spectroscopy

Direct observation of surface polarization at hybrid perovskite/Au interfaces by dark transient experiments - Caram, Jorge; Garcia-Batlle, Marise; Almora, Osbel; Arce, Roberto D.; Guerrero, Antonio; Garcia-Belmonte, Germa (Applied Physics Letters, 2020)
A distinctive feature of hybrid perovskite light-absorbing materials is the non-negligible ionic conductivity influencing photovoltaic performance and stability. Moving ions or vacancies can naturally accumulate at the outer interfaces (electrode polarization) upon biasing. Contrary to that approach, a modulation of conductive or recombination properties could manifest as an alteration in the low-frequency part of the impedance response, either producing inductive or large capacitive features. Under this last view, capacitances are not the response of polarized structures or charging mechanisms, but result from the modulation of currents. This work intends to provide pieces of evidence that assist us in distinguishing between these two dissimilar mechanisms, namely, real charge polarization and delayed current effects under bias in the dark. The analysis relays upon an experimental technique based on transient charging signals using the Sawyer-Tower circuit. Instead of applying an alternating small perturbation over a steady-state voltage (differential capacitance method), transient charging measures the resulting polarization upon a large bias step under the suppression of dc currents. Our findings reveal that real steady-state charge is indeed induced by the applied voltage in the dark, easily interpreted by means of charged real capacitors with values much larger than the geometrical capacitance of the film. The connection between that polarization and the charging of perovskite/contact interfaces is highlighted.
CRIS-Team WoS Importer:2020-05-29

Do Capacitance Measurements Reveal Light-Induced Bulk Dielectric Changes in Photovoltaic Perovskites? - Almora Rodriguez, Osbel; Aranda, Clara; Garcia-Belmonte, Germà (Journal of Physical Chemistry C, 2018)
Several studies have identified complex interactions between photogenerated carriers and the crystal lattice in perovskite materials for photovoltaics, which are considered to have an inherently soft character. Light is known to induce phase segregation in mixed halide perovskites, enhance piezoelectricity, and change dipole moments of the unit cell. Therefore, it is considered that photogenic variations in bulk polarizability and dielectric properties. Light-induced bulk polarization changes should be observable by capacitance measurements, preferably at intermediate frequencies where the geometric capacitance dominates. However, capacitance spectra are influenced by several capacitive and resistive mechanisms, which are thus modulated by light. Capacitances may arise from dielectric bulk polarization, space-charge depletion zones, chemical electronic bulk storage, and interfacial accumulation mechanisms. This variety of capacitive mechanisms may induce wrong interpretation and produce misleading outcomes when uncritically connected to the bulk polarization response. The actual value of the geometric capacitance is shown in the figure below. Careful analyzes are then needed before attributing the light-induced modulation of the measured capacitance to hybrid perovskite dielectric changes. The actual value of the geometric capacitance is shown in the figure below. Careful analyzes are then needed before attributing the light-induced modulation of the measured capacitance to hybrid perovskite dielectric changes. The actual value of the geometric capacitance is shown in the figure below. Careful analyzes are then needed before attributing the light-induced modulation of the measured capacitance to hybrid perovskite dielectric changes.<br

Electrical-Field-Driven Tunable Spectral Responses in a Broadband-Absorbing Perovskite Photodiode. - Tang, Xiaofeng; Matt, Gebhard; Gao, Shuai; Gu, Ening; Almora, Osbel; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Controllably manipulating the spectral response of broadband-absorbing semiconductors is crucial for developing wavelength-selective optoelectronic devices. In this article, we report for the first time, the bias-dependent spectral responses for a metal-halide perovskite photodiode. Tunable external quantum efficiencies in the short- and long-wavelength regimes, and the full spectral range (ca. 300-800 nm) are observed when the device is operated under short-circuit, and forward and reverse bias conditions, respectively. This observation is understood by the interplay of wavelength-dependent penetration depth and barrier formation within the photodiode device stack. The general applicability of this concept is confirmed by a systematic study on a series of mixed-halide perovskite devices. These results suggest that the proposed concept allows as a promising platform and should inspire further exploration of multispectral responsive optoelectronic devices.
Keywords: perovskite; optoelectronics; electrodeposition; mixed-halide perovskite; external quantum efficiency

Ionic Charging by Local Imbalance at Interfaces in Hybrid Lead Halide Perovskites - Almora Rodriguez, Osbel; Guerrero, Antonio; Garcia-Belmonte, Germà (Applied Physics Letters, 2016)
When mixed ionic-electronic conductors are used in optoelectronic devices. Ionic effects in perovskitesolar cells are believed to be distorted. Current hysteresis and switchable photovoltaic characteristics have been linked to the kinetics of ion migration. However, the nature of the specific ionic mechanism (or mechanisms) can not be understood. It is considered that the local rearrangement of the electrode interfaces gives rise to a high degree of apparent capacitive effects. CH3NH3PbI3 samples show two main polarization processes and reveal the structure of the ionic double-layer at the interface with the non-reacting contacts. It is observed that the ionic charging, with a typical response time of 10 seconds, is a local effect confined in the vicinity of the electrode, which entails absence of net mobile ionic concentration (space-charge) in the material bulk.<br
Keywords: organic compounds; ionic conductivity; lead compounds

Ionic Dipolar Switching Hinders Charge Collection in Perovskite Solar Cells with Normal and Inverted Hysteresis - Almora Rodriguez, Osbel; Lopez-varo, Pilar; Cho, Kyung Taek; Aghazada, Sadig; Meng, Wei; Hou, Yi; Echeverria-Arrondo, Carlos; Zimmermann, Iwan; Matt, Gebhard; Jiménez-Tejada, Juan A.; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; et al. (Solar Energy Materials and Solar Cells, 2019)
Drift-diffusion modeling of the ionic dipole switching from the measurement of fast scanned and long pre-biased electrical response is proposed as a novel protocol for evaluation of limit hysteretic effects in perovskite solar cells. Up to eight systems were measured including CH3NH3PbI3, Cs0.1FA0.74MA0.13PbI2.48Br0.39 and FA0.83MA0.17Pb1.1Br0.22I2.98 3D perovskite absorbers, as well as 2D capping layers towards the selective contacts. We show systematic hysteretic patterns, even among typical hysteresis-free devices, including normal and inverted hysteresis as general dissimilar trend between CH3NH3PbI3 and mixed perovskite cells, respectively. Particularly, strong changes in the short-circuit current density (Jsc) were identified, in addition to different trends affecting the fill factor (FF) and the open-circuit voltage (Voc). The changes in Jsc were analyzed with state-of-the-art numerical drift-diffusion simulations concluding in an important reduction in the charge collection due to ionic distribution switching depending on the pre-biasing protocol and the type of absorbing perovskite. It is shown that mixed perovskites inhibit ionic dipolar switching. In addition, our calculi signal on the required conditions for the occurrence of inverted hysteresis and changes in the Voc. Regarding the FF and Voc patterns a new empirical approach is introduced and corresponding interpretations are proposed. <br
Keywords: Perovskite solar cells; Ionic polarization; Hysteresis; Photocurrent

Ion-mediated hopping electrode polarization model for impedance spectra of CH3NH3PbI3 - Almora Rodriguez, Osbel; González-Lezcano, Alfredo; Guerrero, Antonio; Brabec, Christoph J.; Garcia-Belmonte, Germa (Journal of Applied Physics, 2020)
Methylammonium lead iodide (CH3NH3PbI3) is one of the most attractive materials for optoelectronic applications, and it is the most typical absorber in perovskite solar cells, which are unprecedentedly successful devices in terms of power conversion efficiency. In this work, the conductivity and capacitance spectra of symmetrically contacted Au/CH3NH3PbI3/Au thick pellets are measured via impedance spectroscopy at different temperatures in dark equilibrium. The experimental conductivity spectra are parameterized and showed to follow the formalism of hopping DC conductivity in the CH3NH3PbI3 bulk. The presence of several regimes for the general Jonscher's “universal” conductivity–frequency response is highlighted and associated with the ionic–electronic overlapping conductivities. For the capacitance spectra, the general features of electrode polarization capacitance at the CH3NH3PbI3/Au interfaces are identified but yet are found to be in disagreement with some trends of classical ionic conductivity models, unable to separate different contributions. Accordingly, an analytical model is proposed accounting for hopping processes where the low frequency activation energy is split into ionic and electronic components. Our parameterizations and analytical model discern between the bulk/interface and ionic/electronic phenomena and estimate the multiple activation energies in this hybrid halide perovskite.<br
Keywords: Electrodes; Photovoltaics; Perovskites; Dielectric properties; Optoelectronic applications; Electrochemical impedance spectroscopy; Ionic conductivity

Light capacitances in silicon and perovskite solar cells - Almora, Osbel; Garcia-Belmonte, Germà (Solar Energy, 2019)
The framework on which the physics of silicon solar cells (SiSCs) is based robustly predicts dependences of capacitance on light intensity and voltage, even when most recent innovations are considered as the incorporation of transition metal oxide/Si heterojunctions. However, perovskite solar cells (PSCs) challenge most of the established paradigms, claiming for rethinking of known theories and devising novel models. Here we tackle this scenario by probing and comparing light-induced capacitance responses yielded by these two major exponents in the field of photovoltaic research. SiSCs light capacitances can be easily interpreted in the framework of the so-called chemical capacitance. Latest approaches addressing the intriguing low-frequency capacitive features of PSCs are outlined and compared. Here, apparent similarities and differences between both photovoltaic technologies are highlighted, concerning the observation of light capacitances of chemical origin. It is concluded that, contrary to that occurring in SiSCs, bulk electronic chemical capacitances are not straightforwardly observed in PSCs. As capacitive features exhibited by PSCs are believed to be critically connected to performance degradation and device instability, future research and explanation directions are proposed here for advancing in the understanding of this challenging photovoltaic technology.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Capacitance; Dielectric relaxation; Light; Perovskites; Silicon; Solar cells

Light intensity modulated impedance spectroscopy (LIMIS) in all-solid-state solar cells at open-circuit - Almora, Osbel; Zhao, Yicheng; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Garcia-Belmonte, Germà; Brabec, Christoph (Nano Energy, 2020)
Potentiostatic impedance spectroscopy (IS) is a well-established characterization technique for elucidating the electric resistivity and capacitive features of materials and devices. For solar cells, by applying a small voltage perturbation the current signal is recorded and the recombination processes and defect distributions can be accessed. In this work, a photo-impedance approach, named “light intensity modulated impedance spectroscopy” (LIMIS), is first time tested in all-solid-state photovoltaics by individually recording photocurrent (IMPS) and photovoltage (IMVS) responsivity signals due to a small light perturbation at open-circuit (OC), and combining them: LIMIS = IMVS/IMPS. The experimental LIMIS spectra from silicon, organic, and perovskite solar cells are presented and compared with IS. Our theoretical analyses, including equivalent circuit models, show a correction to the lifetimes values by obtaining the total differential resistances and capacitances combining IS and LIMIS. This correction addresses some discrepancies among different techniques, as also shown with photo-induced transient photovoltage. The experimental differences between IS and LIMIS proves the unsuitability of the superposition principle and suggest a bias-dependent photo-current correction to the empirical Shockley equation of the steady-state current at different illumination intensities around OC. In addition, new features are reported for the low-frequency capacitance of perovskite solar cells.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Charge carrier generation rate; Impedance spectroscopy; Light intensity modulation; Perovskites; Photocurrent; Solar cells

Long-Term Field Screening by Mobile Ions in Thick Metal Halide Perovskites: Understanding Saturation Currents - Almora, Osbel; Miravet, Daniel; Gelmetti, Ilario; Garcia-Belmonte, Germa (Physica Status Solidi-Rapid Research Letters, 2022)
Metal halide perovskite-based semiconductor devices with micrometer-to-millimeter-thick perovskite layers show a current response upon polarization which evolves up to several hours, transiting several regimes. This is the case of X-ray detectors where the use of absorber perovskites produces instabilities in the dark reverse saturation current hindering the signal processing. Even though these phenomena are often attributed to the electronic–ionic conductivity and the interface phenomena in these perovskites, a proper theoretical description is missing. Herein, the numerical simulation study reproduces the main experimental trends and explains the origin of some of the apparently-always-increasing current transients in thick perovskite samples. The mobile ion concentration and mobility are correlated with three main transport regimes and interpretation and parameterization are provided to the current saturation time in terms of the ionic screening of the electric field toward the interfaces. The final steady-state under reverse polarization is found as diffusion-limited electronic current, which results from abrupt mobile ion depletion proportional to the Debye length in the vicinity of a contact. The conclusions suggest the material optimization of the contact interfaces as a pathway to reduce the long current saturation times in these devices.
CRIS-Team Scopus Importer:2022-09-30
Keywords: charge carrier mobility; Debye length; drift-diffusion simulations; ionic conductivity; metal halide perovskites; semiconductor interfaces; X-ray detectors

Noncapacitive Hysteresis in Perovskite Solar Cells at Room Temperature - Almora Rodriguez, Osbel; Aranda, Clara; Zarazua, Isaac; Guerrero, Antonio; Garcia-Belmonte, Germà (ACS Energy Letters, 2016)
The current density-voltage (J-V) curves of perovskite solar cells have a hysteresis-like distortion. Hysteresis has raised many concerns about the feasibility and long-term stability of this kind of photovoltaic technology. However, there is a lack of distinction among different hysteretic phenomena which is necessary to unravel its underlying physical and chemical mechanisms. Here we distinguish between capacitive and noncapacitive currents giving rise to specific hysteretic responses in the J-V curves of PSCs. Hysteresis dominates in regular structures with TiO2 as bottom electron selective layer. This is due to the charge, both ionic and electronic, accumulation ability of the TiO2/perovskite interface but no influence on the steady-state operation. Noncapacitive hysteresis is observable at slow enough scan rates in all kind of architectures. Inverted structures, including organic compounds as a result of the inherent reactivity of contact materials and absorbers perovskites.<br

On Mott-Schottky Analysis Interpretation of Capacitance Measurements in Organometal Perovskite Solar Cells - Almora Rodriguez, Osbel; Aranda, Clara; Mas-Marza, Elena; Garcia-Belmonte, Germà (Applied Physics Letters, 2016)
Capacitance response of perovskite-based solar cells (PSCs) can be exploited to underlying physical mechanisms, both in bulk and at outer interfaces. Especially interesting is the use of the depletion layer capacitance theory to PSCs, following common procedures used with inorganic and organic photovoltaic devices. Voltage modulation of the depletion layer allows extracting relevant parameters as the absorber defect density and built-in potential by means of the Mott-Schottky (MS) analysis. However, the uncritical use of the MS technique, commonly observed in PSCs, produces on the measured capacitance value. Avoiding accumulation capacitive parasitic contributions. It is noted that the distinction of capacitance is only feasible in the case of perovskite layers containing significant defect density ( 1017 cm-3). It is confirmed that MS is reproducible by hysteresis reduction at slow scan rates, and positive bias starting polarization. A complete procedure with specific checking points is provided here for consistent MS measurement and interpretation.
Keywords: capacitance measurement; organic compounds; solar cells

Perovskite Solar Cells: A brief Introduction and some Remarks - Almora Rodriguez, Osbel; Vaillant-Roca, Lídice; Garcia-Belmonte, Germà (Revista Cubana de Fisica, 2017)
During the last four years, the spectacular and unprecedented rise of so-called perovskite solar cells (PSCs) in conversion efficiency with low-cost manufacturing processes. The inclusion of perovskite type absorber materials, typically CH3NH3PbI3, has been a key factor in the development of this emerging technology. However, many poorly understood aspects of its operating modes. This paper provides a brief introduction to the structure, materials and characteristics of PSCs. In addition, the state-of-the-art of several subjects of interest is discussed, as well as the hysteresis phenomenon of current-voltage curves.<br
Keywords: Efficiency and performance of solar cells; Organic-inorganic hybrid nanostructures; Semiconductors thin films

Selective Growth of Layered Perovskites for Stable and Efficient Photovoltaics - Cho, Kyung Taek; Grancini, Giulia; Lee, Yonghui; Oveisi, Emad; Ryu, Jaehoon; Almora Rodriguez, Osbel; Tschumi, Manuel; Schouwink, Pascal Alexander; Seo, Gabseok; Heo, Sung; Park, Jucheol; Jang, Jyongsik; et al. (Energy and Environmental Science, 2018)
Perovskite solar cells (PSCs) are promising alternative to clean energy because of their high-power conversion efficiency (PCE) and low materials and processing cost. However, their poor stability and operation still limits their practical applications. Here we design an innovative approach to control the surface growth of a low-dimensional perovskite layer on top of a bulk three-dimensional (3D) perovskite film. This results in a structured perovskite interface where a distinct layered low dimensional perovskite is engineered on top of the 3D film. Structural and optical properties of the cells are realized. When embodying the low dimensional perovskite layer, the photovoltaic cells exhibit an enhanced PCE of 20.1% on average, when compared to pristine 3D perovskite. In addition,<br

Superior Performance of V2O5 as Hole Selective Contact over other Transition Metal Oxides in Silicon Heterojunction Solar Cells - Almora Rodriguez, Osbel; Gerling, Luis Guillermo; Voz, Cristóval; Alcubilla, Ramón; Puigdollers, Joaquim; Garcia-Belmonte, Germà (Solar Energy Materials and Solar Cells, 2017)
Transition metal oxides (TMOs) have recently been proved to efficiently serve as hole-selective contacts in crystalline silicon (c-Si) heterojunction solar cells. In the present work, two TMO/c-Si heterojunctions are explored using MoO3 (reference) and V2O5 as to alternative candidate. It has been found that V2O5 devices present larger (16% improvement) power conversion efficiency mainly due to their higher open-circuit voltage. While V2O5 / c-Si devices with textured front surfaces also have short-circuit currents, it is also known that flat solar cell architectures allow for the V2O5/n-Si interface, giving significant carrier lifetimes of 200 μs (equivalent to a surface recombination velocity of Seff 140 cm s-1) as derived from impedance analysis. As a consequence, a significant open-circuit voltage of 662 mV is achieved. It is found that, at the TMO/c-Si contact, a TMO work function enhancement ΔΦTMO occurs during the heterojunction formation with the consequent dipole layer enlargement Δ'= Δ + ΔΦTMO. TMO/c-Si contact energetics, carrier transport across the interface and surface TMO / c-Si heterojunctions.<br
Keywords: Transition metal oxides; Silicon solar cells; Impedance spectroscopy; Passivation; Minority carrier lifetime

Surface versus Bulk Currents and Ionic Space-Charge Effects in CsPbBr3 Single Crystals - Almora Rodriguez, Osbel; Matt, Gebhard; These, Albert; Kanak, Andrii; Levchuk, Ievgen; Shrestha, Shreetu; Osvet, Andres; Brabec, Christoph; Garcia-Belmonte, Germa (Journal of Physical Chemistry Letters, 2022)
CsPbBr3 single crystals have potential for application in ionizing-radiation detection devices due to their optimal optoelectronic properties. Yet, their mixed ionic-electronic conductivity produces instability and hysteretic artifacts hindering the long-term device operation. Herein, we report an electrical characterization of CsPbBr3 single crystals operating up to the time scale of hours. Our fast time-of-flight measurements reveal bulk mobilities of 13-26 cm(2) V-1 s(-1) with a negative voltage bias dependency. By means of a guard ring (GR) configuration, we separate bulk and surface mobilities showing significant qualitative and quantitative transport differences. Our experiments of current transients and impedance spectroscopy indicate the formation of several regimes of space-charge-limited current (SCLC) associated with mechanisms similar to the Poole-Frenkel ionized-trap-assisted transport. We show that the ionic-SCLC seems to be an operational mode in this lead halide perovskite, despite the fact that experiments can be designed where the contribution of mobile ions to transport is negligible.
CRIS-Team WoS Importer:2022-06-10

Thin-Film Electrostatic Discharge Protection for Highly Segmented OLEDs in Automotive Applications - Bechert, Hermann; Almora, Osbel; Regau, Kilian; Matt, Gebhard; Brabec, Christoph; Wehlus, Thomas (Advanced Materials Technologies, 2019)
Future autonomous driving requires new lighting solutions. Communication in between other cars and pedestrians, which fulfills the requirements of the automotive lighting industry, is needed. A very promising lighting solution for this application are highly segmented organic light-emitting diodes (OLEDs). Unfortunately, small area OLEDs are very sensitive to electrostatic discharge due to the small capacitance of the OLED segments. This study presents a solution for highly segmented OLEDs to fulfill automotive requirements regarding electrostatic discharge (ESD) without cost driving external components but through the improvement of the OLED itself. This solution is designed to be cheap and simple in fabrication, derived from standard photolithography to ensure no impact on existing supply chains and flexible OLED fabrication. After introducing the improved device concept for highly segmented OLEDs and its boundary conditions, a detailed view on the corresponding fabrication steps is given. The capacitive response of the protected OLED segments with respect to OLEDs without the introduced protection layer is characterized via impedance spectroscopy. The results exhibit the functionality of the ESD protection layer and prove with automotive ESD stability requirements complianc
Keywords: OLED; segmentation; ESD protection; impedance spectroscopy; capacitance; automotive rear-light

Unraveling the Microstructure-Related Device Stability for Polymer Solar Cells Based on Nonfullerene Small-Molecular Acceptors - Du, Xiaoyan; Heumüller, Thomas; Gruber, Wolfgang; Almora, Osbel; Classen, Andrej; Qu, Jianfei; He, Feng; Unruh, Tobias; Li, Ning; Brabec, Christoph (Advanced Materials, 2020)
As the power conversion efficiency (PCE) of organic solar cells (OSCs) has surpassed the 17% baseline, the long-term stability of highly efficient OSCs is essential for the practical application of this photovoltaic technology. Here, the photostability and possible degradation mechanisms of three state-of-the-art polymer donors with a commonly used nonfullerene acceptor (NFA), IT-4F, are investigated. The active-layer materials show excellent intrinsic photostability. The initial morphology, in particular the mixed region, causes degradation predominantly in the fill factor (FF) under illumination. Electron traps are formed due to the reorganization of polymers and diffusion-limited aggregation of NFAs to assemble small isolated acceptor domains under illumination. These electron traps lead to losses mainly in FF, which is in contradistinction to the degradation mechanisms observed for fullerene-based OSCs. Control of the composition of NFAs close to the thermodynamic equilibrium limit while keeping adequate electron percolation and improving the initial polymer and NFA ordering are of the essence to stabilize the FF in NFA-based solar cells, which may be the key tactics to develop next-generation OSCs with high efficiency as well as excellent stability.
CRIS-Team Scopus Importer:2020-03-10
Keywords: bulk-heterojunction microstructure; morphology stability; nonfullerene acceptors; organic solar cells; photostability

Utilization of Temperature-Sweeping Capacitive Techniques to Evaluate Band Gap Defect Densities in Photovoltaic Perovskites - Almora Rodriguez, Osbel; García-Batlle, Marisé; Garcia-Belmonte, Germà (Journal of Physical Chemistry Letters, 2019)
Capacitive techniques, routinely used for solar cell parameter extraction, probe the voltage-modulation of the depletion layer capacitance isothermally as well as under varying temperature. Also defect states within the semiconductor band-gap respond to such stimuli. Although extensively used, capacitive methods have found difficulties when applied to elucidate bulk defect bands in photovoltaic perovskites. This is so because perovskite solar cells (PSCs) actually exhibit some intriguing capacitive features hardly connected to electronic defect dynamics. The commonly reported excess capacitance observed at low frequencies is originated by outer interface mechanisms and has a direct repercussion on the evaluation of band-gap defect levels. Starting by updating previous observations on Mott-Schottky (MS) analysis in PSCs, it is discussed how the thermal admittance spectroscopy (TAS) and the deep level transient spectroscopy (DLTS) characterization techniques present spectra with overlapping or even “fake” peaks caused by the mobile ion-related, interfacial excess capacitance. These capacitive techniques, when used uncritically, may be misleading and produce wrong outcomes.<br